2001
DOI: 10.1007/bf02723244
|View full text |Cite
|
Sign up to set email alerts
|

Brush cytology: An adjunct to diagnostic upper GI endoscopy

Abstract: Endoscopic brush cytology (EBC) was performed in antral and duodenal brushings of children subjected to upper GI endoscopy for the detection of H. pylori (Hp) and trophozoites of Giardia lamblia (Glt) in addition to routine endoscopic grasp biopsy (EGB). It was hospital based prospective study. EBC was performed in children subjected to upper GI endoscopy with a sheathed cytology brush. Mucosal brushings were collected from antrum, body of the stomach and second or third part of duodenum by gently rubbing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Furthermore, although we did not design the study to validate Gram staining of smears versus culture results, we identified microscopically H. pylori forms in most specimens of infected individuals, thus providing another independent assessment of H. pylori status. Several studies comparing endoscopically obtained specimens for culture and microscopy have found agreement between culture and cytology . Clearly, orogastric bush staining provides a nonendoscopic alternative to current practices and potentially extends the ability to collect culture samples from sites where endoscopy is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although we did not design the study to validate Gram staining of smears versus culture results, we identified microscopically H. pylori forms in most specimens of infected individuals, thus providing another independent assessment of H. pylori status. Several studies comparing endoscopically obtained specimens for culture and microscopy have found agreement between culture and cytology . Clearly, orogastric bush staining provides a nonendoscopic alternative to current practices and potentially extends the ability to collect culture samples from sites where endoscopy is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that the cytopathological techniques have better diagnostic yield. Work by Bendig et al and Patwari et al advocates the use of cytological methods such as duodenal brush cytology over stool examination. Panarelli et al applied morphometric technique and found that giardia trophozoites are more numerous and better visualised in cytology preparations as compared to tissue section with a significant P ‐value (< .05).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to other Histological Features (Nongraded Variables) Eidt S developed a perspective which identifies surface epithelial damage, mucous depletion, and erosions. Our study was compared with study [14], These may be striking features in some cases of active H. pylori chronic gastritis. They have also mentioned that lymphoid aggregates with germinal centers are characteristic of chronic H. pylori gastritis and a hallmark of this diagnosis.…”
Section: : Graphical Representation Of Graded Variable and Its Association With H Pylorimentioning
confidence: 98%
“…They have also mentioned that lymphoid aggregates with germinal centers are characteristic of chronic H. pylori gastritis and a hallmark of this diagnosis. The comparative analysis of different graded variables between Ahluwalia et al [14]. Afzal et al [15] Table 2.…”
Section: : Graphical Representation Of Graded Variable and Its Association With H Pylorimentioning
confidence: 99%
See 1 more Smart Citation